China released the Action Plan on Prevention and Control of Soil Pollution - Zhang, Fang; Li, Guanghe (Frontiers of environmental science & engineering, 2016)
China released the Action Plan on Prevention and Control of Soil Pollution （i.e. ＂Soil Ten Chapters＂） on May 31st 2016. The plan aims to arrest the worsening situation by 2020, improve the soil quality with a comprehensively controlled risk by 2030, and form a virtuous ecosystem cycle by 2050. According to the plan,